Integration of Transferable Life Skills into Modern Tourism Curricula: Post-Pandemic Insights - Abhijaat Sahu,; Somnath Datta,; Joymalya Bhattacharya, (AG Volumes, 2026)
The current study is about the incorporation of transferable life skills into the contemporary tourism curriculum in the realm of the post-pandemic environment, where it is critical to note that the trade-off between technical proficiency and human-centered skills ought to be established to ensure the workers are more resilient. The paper examines the weaknesses of the curricula and the labor preparation, which takes into consideration the synthesis of the secondary information, the national skill gap assessment and international policy reports by means of a descriptive conceptual approach. Not only do the findings demonstrate the topicality of the skills of communication, adaptability, empathy, problem-solving, resilience and digital human interface in relation to graduate employability and career mobility, but they also reveal that there are still gaps in the system since the curriculum is still fragmented and the transferable skills are not implemented but rather prioritized. As it was stated by the European Travel Commission (2023) as well as the Tourism and Hospitality Skill Council (2024), there are not many discrepancies between the expectations of the employers and the skills that one can possibly gain at the workplace; the activities of tourism are compatible in a certain way. However, it is also observed that at the same time, in the absence of formal systems to reflectively inculcate such competences in learning. The report proposes a balance model in curriculum, which incorporates, in the support of industry-academia collaboration, both the life and technical skills, flexible certification and the further professional development of the instructors. The paper has offered pertinent information to the making of the curriculum and policy development through the redefinition of tourism education as an strategic platform for skill development rather than a highly vocational career path. Lastly, the transferable life skills should also be incorporated in the tutoring program of tourism to have graduates who are future-ready, adaptable and able to work in every one of the service economies.